The determination of iron levels in Menthae tea (Mentha piperita L.) - Mandal, Sačira; Kešković, Nejra; Marevac, Naida (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2017)
Menthae tea (Mentha piperita L.) is one of the most widely consumed herbal teas. This tea is recognized as a drink that may have several health benefits, primarily due to the presence of nutritional elements especially essential micro and ultramicro elements. In this study, we investigated the content of iron in mentha tea samples found in a local market in Sarajevo. The preparation of the samples was done by dry digestion in triplicate while levels of iron were analyzed by spectrophotometry. The amounts of iron were ranged from 275.6 mg Fe/kg to 354.6 mg Fe/kg. The used spectrophotometric method is simple and sensitive method that can be applied for the determination of total Fe content in plant material.